My first and only love - Khalīfah, Saḥar (Hoopoe, an imprint of The American University in Cairo Press, 2021)
"Nidal, after many decades of restless exile, returns to her family home in Nablus, where she had lived with her grandmother before the 1948 Nakba that scattered her family across the globe. She was a young girl when the popular resistance began and, through the bloodshed and bitter struggle, Nidal fell in love with freedom fighter Rabie. He was her first and only real love--him and all that he represented: Palestine in its youth, the resistance fighters in the hills, the nation as embodied in her family home and in the land."--